Challenging the Dichotomy The Licit and the Illicit in Archaeological and Heritage Discourses - Watkins, Joe; Gnecco, Cristobal; Field, Les (University of Arizona Press, 2016)
"Challenging the Dichotomy" explores how dichotomies regarding heritage dominate the discourse of ethics, practices, and institutions. Examining issues of cultural heritage law, policy, and implementation, editors Les Field, Cristóbal Gnecco, and Joe Watkins guide the focus to important discussions of the binary oppositions of the licit and the illicit, the scientific and the unscientific, incorporating case studies that challenge those apparent contradictions.Utilizing both ethnographic and archaeological examples, contributors ask big questions vital to anyone working in cultural heritage. What are the issues surrounding private versus museum collections? What is considered looting? Is archaeology still a form of colonialization? The contributors discuss this vis-à-vis a global variety of contexts and cultures from the United States, South Africa, Argentina, New Zealand, Honduras, Colombia, Palestine, Greece, Canada, and from the Nasa, Choctaw, and Maori nations."Challenging the Dichotomy" underscores how dichotomies-such as licit/illicit, state/nonstate, public/private, scientific/nonscientific-have been constructed and how they are now being challenged by multiple forces. Throughout the eleven chapters, contributors provide examples of hegemonic relationships of power between nations and institutions. Scholars also reflect on exchanges between Western and non-Western epistemologies and ontologies.The book's contributions are significant, timely, and inclusive. "Challenging the Dichotomy" examines the scale and scope of "illicit" forms of excavation, as well as the demands from minority and indigenous subaltern peoples to decolonize anthropological and archaeological research.